The Preservice Teachers' Approaches Toward Incorrect Probability Problems - Korkmaz, Ebru; Alkan, Selcuk (Sage Publications Inc, 2023)
Identifying the mistakes in student responses and being able to manage the solution process are among the fundamental skills that should be acquired by the pre-service teachers. This skill is important in probability, about which students have a great number of misconceptions. The aim of this study was to determine the misconceptions in the student answers given by the researcher about probability and to examine the solution explanations of the preservice teachers. In this context, the student answers containing five wrong solutions were examined. Case study, one of the qualitative research methods, was used. Forty-two third grade preservice mathematics teachers participated in the study. A task-based interview was used in the study. The findings revealed that the participants were able to recognize simple and discrete probability problems more easily and provided correct solutions; however, they had difficulty in determining the universal space independent events and failed to detect the mistakes in the student answers successfully. As a result of the research, it was concluded that the importance attached to procedural knowledge should also be given to conceptual knowledge, what a concept means as well as what it does not mean should be explained, open-ended questions that will increase the power of reasoning should be used instead of typical problems, and more effective learning should be carried out by using different teaching methods and techniques.
Keywords: probability; problem; preservice teachers; elementary school mathematics; misconceptions